Novalis German Poet-European Thinker-Christian Mystic - Hiebel, Friedrich, 1903-1989; Project Muse; Project Muse. (Project Muse, 2020)
Originally published in 1954, Hiebel's Novalis was the first critical evaluation in English of the life and works of Novalis (1772-1801), the German Romantic poet of the Blue Flower, since Thomas Carlyle's essay in 1829. This book presents not only a fully rounded picture of the man, the philosopher and scientist, the writer of beautiful fairy tales, the mystic poet of Christianity, but also a thoughtful commentary on one of the most influential and fruitful periods in German intellectual life. Hiebel combines the exactness required of the scholar with the creative writer's intuitive appreciation of a great poet's works.
A condensed version, in English, of the author's Novalis, der Dichter der Blauen Blume.
Issued as part of book collections on Project MUSE.
"Essays and studies about Novalis and his age, published in the United States and Great Britain."
"Editions of Novalis' works in the English language."
Description based on print version record.
Keywords: Novalis, -- 1772-1801.; Electronic books; Electronic books